HUBUNGAN ANTARA KINERJA PERAWAT DENGAN KEPUASAN PASIEN RAWAT INAP DI RSUD H ABDUL MANAP KOTA JAMBI TAHUN 2020 - Devi Yusmahendra; Yusnilawati (Universitas Adiwangsa Jambi, 2021)
Public confidence in the hospital can be seen from the public satisfaction index. One aspect that determines public trust is the performance of nurses. Based on hospital satisfaction index data, hospitalization shows less satisfied performance. This study aims to determine the picture of the relationship between nurse performance with patient satisfaction. This research uses cross sectional design which is implemented in RSUD Abdul Manap Jambi On Date 8 to 26 february 2020, the number of respondents is 84 respondents. Instruments in this study using questionnaires. Data analysis used is univariate and bivariate analysis by using chi-square test. Result of analysis of nurse performance good as many as 51 respondents (60,7%), less good counted 33 respondents (39,3%) and satisfied respondent as much as 55 respondents (65,5%), felt unsatisfied as much 29 respondents (34.5%). Chi Square Test results there is a significant relationship between nurse performance with patient satisfaction with P-Value of 0.002. With the high value of good nurse performance it will create high patient satisfaction.